Modelling The History Of Sultan Nuku’s Struggle In The Design Of Historical Tourism Area In Tidore City - Hery Purnomo; M. Amrin Conoras; Endah Harisun; Nurul Hikmah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Tidore is a Sultanate in North Maluku which is part of the Four Sultanates of Maluku Kie Raha, Moluku Kie Raha is a term to refer to four regional rulers called kolano: Ternate, Tidore, Bacan, and Jailolo. The golden age of the Sultanate of Tidore spanned a wide area, most of Maluku to the East, the Papua region, rich in historical and cultural heritage. Efforts that can be made in order to maintain and preserve historical relics are by modeling a museum of the history of the struggle of Sultan Nuku, so that the next generation can still witness historical evidence of the legacy of previous generations. Qualitative design methods are used in designing by collecting data, analyzing data, concepts, and modeling designs. With the modeling of the Nuku Sultanate history museum, it is expected to increase the power to provide an overview of the history of the Nuku Sultanate in Tidore.